1976
DOI: 10.1128/iai.14.1.47-54.1976
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte transformation and interferon production in human mononuclear cell microcultures for assay of cellular immunity to herpes simplex virus

Abstract: Interferon production and transformation in respowse to herpes simplex virus antigen were studied in microcultures of human mononuclear cells. Mononuclear cells consisting of monocytes and both T and B lymphocytes were purified by Ficoll-Hypaque gradients. Lymphocytes, predominantly T with 5% B, were obtained by passage of buffy-coat cells through nylon fiber columns. For some experiments, autochthonous macrophages and column-purified lymphocytes were stimulated with herpesvirus antigen. The effect of specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…The serum interferon assay was performed on serum obtained from heparin stabilized blood. The assay was performed by using a micromethod, as previously described (Haahr et al 1976). The interferon titer was the the highest dilution that reduced the vesicular stomatitis virus cytophatic effect by 50%.…”
Section: Interferon Assaymentioning
confidence: 99%
“…The serum interferon assay was performed on serum obtained from heparin stabilized blood. The assay was performed by using a micromethod, as previously described (Haahr et al 1976). The interferon titer was the the highest dilution that reduced the vesicular stomatitis virus cytophatic effect by 50%.…”
Section: Interferon Assaymentioning
confidence: 99%
“…Interferon has been found to be one of the mediators of cell-mediated immunity (7,10,20). It is produced in vitro upon exposure of human or mouse leukocytes to mitogens and to viral or nonviral antigens (4,6,9,18…”
Section: Y Ito Et Almentioning
confidence: 99%
“…In 1966, Glasgow provided the first direct evidence of the fact that immunity and immune mechanisms are intimately associated with interferon production (10). Subsequent experiments demonstrated that nonviral antigens stimulated interferon production in cultures of lymphocytes from sensitized donors but not in cultures from donors who lack sensitivity to those antigens (4,6,9).…”
mentioning
confidence: 99%
“…These findings were unexpected as it seemed probable that the responding cell in the UF population was a T cell. However, Haahr et al [6] have noted a reduced response to HSV of nylon wool purified T cells as compared to UF cells 1-12 weeks after a recurrent infection although the response was not related to the time since the onset of the infection.…”
Section: Responses Of Nylon Wool Separated T Lymphocytes In Herpetic mentioning
confidence: 95%
“…The cell type responsible for each response has not been previously determined in man. Immune specific interferon is released in response to HSV antigens by sensitized human T lymphocytes and autologous macrophages [6]. Depletion of T cells in mice increases their susceptibility to herpetic infection, but resistance can be restored by transfer to T cells [13,15].…”
mentioning
confidence: 99%